Urgensi Penerapan Pendidikan Moral di Masyarakat - Fatmawati, Fifi; Fadillah, Nuzulul; Kurnia, Heri (Jurnal Pendidikan Kewarganegaraan dan Politik, 2024)
Moral education is a planned effort carried out by someone to change attitudes, behaviors, and actions carried out by someone so that they are able to interact with their environment, in accordance with the values ​​and morals that already exist in society. Moral education will also make a child more humane. This means that moral education does not only teach about academics, but moral education also teaches non-academics, especially about attitudes in everyday life. Moral education aims to increase the capacity for how to think and make decisions morally. The purpose of moral education itself emphasizes the method of moral consideration to help a child understand what is the basis for accepting a value